Pengaruh Struktur Aset, Ukuran Perusahaan, Risiko Bisnis, dan Likuiditas Terhadap Kebijakan Hutang Pada Perusahaan Property dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Hardini Ariningrum; Eka Junia (Komunitas Dosen Indonesia, 2023)
This study aims to determine the effect of asset structure, firm size, business risk, and liquidity on debt policy. The population used is property and real estate companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses purposive sampling, and there are 45 companies that meet the criteria. This research is a quantitative research with data analysis technique used is multiple regression analysis using IBM SPSS Statistics 25 software as a test tool. The results of the study show that asset structure and firm size have no effect on debt policy, while business risk and liquidity affect debt policy